Participatory mapping and approaches in health and environment (Sustainability in Debate, 2018)
This study aimed to present a map about the environment and its relationship with health, based on the experiences and interrelations of health service workers in the city of Porto Alegre / Brazil. This proposal presents methodological alternatives for the approximation of health surveillance activities with primary health care. The participative approach of action-research was conceived as the main strategy for this study. The work served as a starting point for the evaluation and monitoring of specific situations about environmental health. Besides that, the mapping approach has the potential to establish partnerships for action in the field of health in local territorial context.